2019
DOI: 10.1177/1179550619888856
|View full text |Cite
|
Sign up to set email alerts
|

Deranged Pulmonary Function Tests in Allergic Rhinitis in North Indian Patients

Abstract: Introduction:Significant associations between allergic rhinitis and bronchial asthma have been established and as a result of bronchial hyper-responsiveness, patients can have deranged pulmonary function tests. We aim to compare previous such studies with the result of our study done in India wherein we identify among allergic rhinitis patients who despite not having overt asthmatic symptoms, have pulmonary function derangements, quite possibly at a subclinical disease level.Materials and Methods:We studied 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Monga dan kawankawan menjelaskan bahwa hasil yang didapatkan dapat bervariasi dengan studi lainnya bergantung pada karakteristik populasi yang diteliti dan tingkat layanan kesehatan dari populasi yang diteliti. 27 Gejala rinitis alergi yang paling banyak ditemukan pada pasien rinitis alergi dengan riwayat asma berupa gejala bersin-bersin sebanyak 13 orang (100%) diikuti dengan rinore 10 orang (76,9%) dan hidung tersumbat juga sebanyak 10 orang (76,9%). Hasil penelitian oleh Jaggi et al di India tahun 2019, menunjukkan hasil yang selaras.…”
Section: Pembahasanunclassified
“…Monga dan kawankawan menjelaskan bahwa hasil yang didapatkan dapat bervariasi dengan studi lainnya bergantung pada karakteristik populasi yang diteliti dan tingkat layanan kesehatan dari populasi yang diteliti. 27 Gejala rinitis alergi yang paling banyak ditemukan pada pasien rinitis alergi dengan riwayat asma berupa gejala bersin-bersin sebanyak 13 orang (100%) diikuti dengan rinore 10 orang (76,9%) dan hidung tersumbat juga sebanyak 10 orang (76,9%). Hasil penelitian oleh Jaggi et al di India tahun 2019, menunjukkan hasil yang selaras.…”
Section: Pembahasanunclassified
“…Individuals with allergic rhinitis (AR) frequently have co-existing asthma (estimated at 10-40%) (17), while another 45% of AR individuals without asthma have bronchial hyperresponsiveness (18), an intermediate step toward asthma development. Selected studies have observed that individuals with AR can have an abnormal pulmonary function test (PFT) (19)(20)(21)(22)(23)(24) and fractional excretion of nitric oxide (FeNO) (25)(26)(27)(28)(29) even in the absence of asthma, suggesting that pollen is an important trigger for lower airway inflammation. In addition, FeNO has been shown to increase in sensitized individuals at times of higher pollen counts (27) and has been associated with the number of positive reactions on the SPT (25).…”
Section: Study Rationale For the Six Health Outcomes Pulmonary Outcomesmentioning
confidence: 99%